A framework for reservoir restoration in The Midwest - Dirks, Harrison P. (Kansas State University, 2020)
Reservoirs are built to provide local flood control and recreational activities, but those benefits are often short lived due to the severe ecohydrological problems which come with the process of damming up a watershed. Issues such as sediment deposition, accelerated erosion and loss of natural flood plain will eventually hinder the reservoir from being used for recreation, and significantly decrease its flood storage capacity (Keane, 2019). These are not issues which will correct themselves overtime. In fact, they will begin to rapidly decrease the lifespan of the reservoir, as well as create more problems in the watershed both up and downstream of the dam. For these reasons, scientists and designers have been developing processes for reservoir assessment and restoration which aim to identify issues, and improve reservoir function. Depending on their field of expertise, reservoir exerts have different approaches for both reservoir assessment and restoration. This report explores an alternative approach to reservoir assessment and restoration which aims to layer new information about reservoir function on top of the pre-existing knowledge of reservoir experts.
Keywords: Reservoir Restoration; Reservoir Analysis; Landscape Architecture